Conception et mise en oeuvre d’un dispositif de contrôle automatisé d’une irrigation à l’aide d’Oyas comme milieu poreux - HAMAMI, Habib (My University, 2024)
This project presents the design and implementation of an intelligent irrigation system for precision agriculture. Based on an ESP32 microcontroller, the system integrates various sensors (soil moisture, water level, ambient temperature, and humidity) to automate irrigation. The valve and the pump are controlled via the Blynk application, enabling remote management. The project aims to optimize water consumption while enhancing crop efficiency, addressing the needs of arid regions.